Perioperative and early rehabilitation outcomes following osseointegration in UK military amputees. Issue 5 (17th May 2019) - Wood, Paul; Small, C; Mahoney, P
Abstract : Introduction: This paper examines the pain management, from surgery to specialist rehabilitation, of the first seven military transfemoral amputee patients treated in the UK with femoral osseointegration. All the patients had sustained complex ballistic injuries on the battlefield. The patients were characterised by long-standing problems with functional rehabilitation due to limitations with conventional prostheses, including stump soft tissue issues and impaired biomechanics. Methods: A prospective service investigation was undertaken to evaluate the effectiveness of the pain management of patients undergoing osseointegration. Data were collected by daily direct patient contact, supplemented by a focused review of perioperative and rehabilitation case notes. Physiological and medication details were recorded with specific reference to systemic and regional analgesia and the impact of postoperative complications, including infection and accidental injury. Results: Seven patients underwent femoral osseointegration and were followed up for a period of up to 3 years following surgery. The perioperative recovery was associated with significant escalation of analgesic requirements. Postoperative systemic inflammatory response syndrome was identified in six patients, with wound infection persisting in some cases into the rehabilitation phase. Three patients suffered femoral fractures following accidental injuries secondary to increased mobilisation following surgery. Conclusions: Successful surgical outcomes were achieved in a difficult patient cohort disadvantaged by previously restricted functional recovery from complex injuries. The importance of supporting the operative and recovery phases with a multidisciplinary pain service is emphasised. We offer this data and the lessons learnt to assist clinicians contemplating the establishment and service development of osseointegration services.